PENERAPAN PROJEK PENGUATAN PROFIL PELAJAR PANCASILA DALAM PENGEMBANGAN KREATIVITAS SISWA - Muh. Bahly Basri; Syamsinar; Setiawan, Nurwahda; Amanah, Hafidzatul (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to describe the implementation of the Pancasila Student Profile Strengthening Project (P5) in increasing students' motivation to explore innovative ideas. This research uses a qualitative approach. The research subjects are students and teachers who are directly involved in P5. Data collection was done through structured interviews and document analysis. Data were analyzed through the stages of data reduction, data presentation, and conclusion drawing. The results showed that the implementation of P5 plays a role in improving students' creativity, collaboration, and character. P5 also creates a supportive learning environment to express students' innovative ideas. In addition to academic aspects, students' social skills are also explored in the implementation of P5. In addition, various obstacles were found, such as time management (scheduling), student group dynamics, and adaptation by teachers.